Frequency and Sociodemographic Factors Associated with Congenital Malaria at the Borgou Regional University Teaching Hospital (CHUD-B) in Benin in 2015 - Noudamadjo, Alphonse; SAGBO, GODONOU GRATIEN; Adedemy, Julien Didier (My University, 2017)
Background: Every minute a child dies from malaria in Sub-Saharan Africa. Despite this high infant and child mortality associated with malaria, congenital malaria is still not adequately understood as regarding its frequency, severity and management. The objective of this research work was to determine the frequency and identify the socio-demographic factors associated with the onset of congenital malaria at the gynecological and pediatric units of the Borgou Regional Teaching Hospital (CHUD-B) in Benin in 2015. Methods: This study was a cross-sectional survey with analytical purpose, based on exhaustive census performed from April to July 2015 on newborns delivered at CHUD-B and their mothers. The dependent variable was the presence of congenital malaria and the independent variables were socio-demographic characteristics. The data were processed and analyzed using Epi Info software version 7.0 with a significant threshold of 0.05. Findings: The frequency of congenital malaria in newborns was 19%. No sociodemographic factor was associated with congenital malaria. Conclusion: Nearly one in five newborns delivered at CHUD-B had congenital malaria. Due to malaria’s contribution to perinatal morbidity and mortality and subsequent receptivity of child victims to malaria, a longer study covering a whole year and focused on the determinants of congenital malaria should be carried out
Keywords: Congenital Malaria; Socio-Demographic Factors; Benin